Solid-state structures and thermal properties of inclusion complexes of the organophosphate insecticide fenitrothion with permethylated cyclodextrins - Cruickshank, Dyanne (2010)
The X-ray crystal structures and thermal stabilities of the inclusion complexes formed between the organophosphate insecticide fenitrothion [O,O-dimethyl O-(3-methyl-4-nitrophenyl) phosphorothioate] and the host compounds TRIMEA and TRIMEB (permethylated α- and β-cyclodextrins, respectively) are reported. In the complex (TRIMEA)2·fenitrothion 1, the guest phosphate ester group is disordered and the molecule is fully encapsulated within a novel TRIMEA dimer in which the secondary rims of the two host molecules are in close contact. In contrast, the complex TRIMEB·fenitrothion 2 is monomeric and the guest molecule is statistically disordered over two positions, with the phosphate group inserted in the host cavity in both cases. Thermal analysis indicated gradual and partial loss of the guest in 1 during heating between 130 °C and the melting point of the complex (∼200 °C), whereas complex 2 displayed significant mass loss only after fusion of the complex at 161 °C.